The Influence of Work Environment, Promotion, and Job Satisfaction on Employee Performance - Tasman Tasman; Zulkifli Musannip Efendi Siregar; Meisa Fitri Nasution (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study was to determine the effect of work environment and promotion and job satisfaction as an intervening variable on employee performance. The sample in this study amounted to 34 people.  The research was conducted at PT. Cakra Adi Dharma in Kotapinang, South Labuhanbatu.  The data analysis technique used is path analysis.  The results of the hypothesis test show that the work environment has a positive and significant effect on job satisfaction. Partially Job Promotion has a Positive and Significant effect on Job Satisfaction. Work environment has a positive and significant effect on work performance.  Job Promotion has a Positive and Significant effect on Work Performance.  We suggest that PT Cakra Adi Dharma improve employee performance by improving a better work environment, promotions, and increasing employee job satisfaction.